Video Educative Learning to Improve Listening and Speaking Skills of English by Imitate the Native Speaker - Rinta Aryani; Fifit Rizkiyani (Universitas Muhammadiyah Semarang, 2017)
English is a foreign language in Indonesia. the development of globalization gives many impacts in many fields, including in education. Education in the 21st century is one of the examples of globalization era. Learning in the 21st century has a challenge especially learn about English as a foreign language. One of the challenges is how to increase the English skills of the students. Technology is one of the opportunities of the globalization era to face the challenge of the 21st century. In this research, video educative on YouTube is used as a media in the English learning process. The aim of this media is to improve the listening and speaking skills. The students watched the English video educative first that is uploaded by a native speaker. They will listen how each word is pronounced, then they will retell what they have already heard by making a video. This video has a purpose of improving speaking skill by remembering on the video education that the students' have heard. The objects of this paper are the students of English Department, Semarang State University. This paper uses the descriptive qualitative method. Data is collected by interview and observation activity as primary data and also other sources that related to the paper as a secondary data. The result of the study is students can improve their listening and speaking skills of English by using video educative on YouTube, so they can increase their capability in English.